Employment and the structure of the Finnish economy: a model for evaluating scenarios - Johnny Åkerholm; Timo Hämäläinen; Mika Kuismanen (Bank of Finland, 1995)
In this paper a simple and transparent macroeconomic model is developed for the evaluation of alternative macroeconomic scenarios.With the help of the model it is evaluated how fast economic growth and what kind of structure of demand and supply is needed in order to reduce unemployment to 200 000 persons by the year 2000 given both the government budget and external constraints.The model includes 138 variables: 5 behavioral equations, 75 identities, and 58 exogenous variables.The model simulations suggest the following conclusions.The target to reduce unemployment rate to about 8 per cent can be reached only if annual economic growth is relatively fast, more than 6 per cent, and relies heavily on private services.It is not possible to reduce the indebtedness of the public sector very quickly, because public transfers or tax reliefs are needed to support private consumption. Wages can rise only modestly in order not to allow the current account to worsen too much.Nominal earnings per employee can rise only 5 per cent.With assumed 2 per cent inflation rate real wages can then increase 3 per cent.This is 0.5 percentage units less than the growth of labour productivity.
URN:NBN:fi:bof-20140807257
Keywords: 330